The Climbing Activities of Gunung Gede Pangrango Nasional Park: Aktivitas Pendakian Taman Nasional Gunung Gede Pangrango - andy supriady; Nancy Trisari Schiff; Muhammad Ramadhani (Journal of Physical and Outdoor Education, 2022)
The purpose of this study was to determine the motives, motivations, and benefits for climbers and for the surrounding community of mountaineering activities on Gunung Gede Pangrango. The research was conducted in Gunung Gede Pangrango National Park, West Java Province. This research is a qualitative study that uses a phenomenological approach. Data analysis techniques are observation, interview, and documentation. In this study found three themes in mountaineering activities, namely: Activity motives: 1) want to unwind from the routine of daily activities; 2) want to enjoy the natural scenery; 3) try something new; 4) want to interact with nature; 5) as a hobby. 2. Activity motivation: 1) to get satisfaction; 2) want to reach high places and see nature; 3) want to get new experiences. 3. Benefits of activity: 1) physical training or exercise, 2) recreation to get pleasure, 3) revitalize the mind and physical relaxation, 4) get closer to God; 5) learn to live independently; 6) character building; 7) make new friends; 8) as a means of socializing. The findings of this study reveal that people who carry out Gunung Gede Pangrango climbing activities with the motive and motivation for recreation in order to relieve fatigue from the busyness of daily activities by enjoying the beautiful phenomenon of Gunung Gede Pangrango.